Inventory of Mammals using Camera Traps: A Baseline Study for an Ecosystem Restoration Concession in the Bukit Tigapuluh Landscape, Sumatra - Subrata, Sena Adi; Mossbrucker, Alexander Markus (Tropical Natural History, 2022)
An inventory of resident mammal species was conducted in an ecosystem restoration concession located roughly in the geographical center of the Indonesian island of Sumatra. To assess the diversity of the resident mammalian fauna in major habitat types and to establish baselines for future monitoring programs, two camera trap surveys were implemented. The result of both surveys was similar, revealing the presence of a large variety of native mammals with 32 species of 15 different families, 56% of which are listed as either Vulnerable, Near Threatened, Endangered, or Critically Endangered on the IUCN Red List of 2019. Overall, the encountered diversity of mammal species indicates that the surveyed concession is still comparatively intact and suitable as a habitat for native animals and confirms the importance of the area for mammal conservation in the region.